Design of comb-shaped single-electron slime mold circuit and its application to traveling salesman problem. Issue 6 (2nd November 2022) - Matsuoka, Takuya; Oya, Takahide
Abstract : We propose a single-electron (SE) information processing circuit that mimics the behavior of slime mold. While SE circuits have advantages such as parallel processing and low power consumption, a suitable information processing method has not yet been established for them. Thus, we focus on the behavior of slime mold to develop a suitable information processing method. Reportedly, slime molds can solve the traveling salesman problem (TSP) if their behaviors (i.e. stretching and shrinking) are harnessed. In a simulation results, our information processing method for SE circuits mimics a series of slime mold behaviors to derive the optimal solutions for the TSP. GRAPHICAL ABSTRACT: UF0001